If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(8n + -3) = -12 + 7n Reorder the terms: 4(-3 + 8n) = -12 + 7n (-3 * 4 + 8n * 4) = -12 + 7n (-12 + 32n) = -12 + 7n Add '12' to each side of the equation. -12 + 12 + 32n = -12 + 12 + 7n Combine like terms: -12 + 12 = 0 0 + 32n = -12 + 12 + 7n 32n = -12 + 12 + 7n Combine like terms: -12 + 12 = 0 32n = 0 + 7n 32n = 7n Solving 32n = 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. 32n + -7n = 7n + -7n Combine like terms: 32n + -7n = 25n 25n = 7n + -7n Combine like terms: 7n + -7n = 0 25n = 0 Divide each side by '25'. n = 0 Simplifying n = 0
| n/7=4/3 | | X^2(2x+3y-6)= | | 0=-16t^2+16t+672 | | cos(2x)*sin(4x)=0 | | -2x-4.5+7=1.8 | | 3/x=18 | | r/3=4/2 | | 12-7x=24x+23 | | 2/x=3 | | -3u=30 | | 3/x=5/3 | | 5m^2-3m+4=0 | | 6*(6+4)=7*(x+7) | | 4*(6+4)=7*(x+7) | | 7-4x+3+2x=6 | | -2-4x=13-7 | | 5/v=7/4 | | 3(4m+4)=-30-2m | | (3x^2+4y)-(2x^2-6y)= | | 0.33+X=W | | f(x)=-x^3-4x^2+7 | | 2x^3+1=x^2+2x | | 5+7=22 | | 1/2(h+8)(h)=42 | | 3*(5+3)=4*(x+4) | | 2x-1=-1+2x | | -12+16y=224 | | 5+11x=3-2x | | 5+11x=3-5 | | 5p-6=p+2p | | 3/4-(2/3*1/3+1/9)/4/9 | | .23x-x=82 |